Tata Kelola Kolaboratif Sampah Perkotaan: Analisis Model Triple Helix di Kota Pesisir Dumai - Mardiana Mardiana; Zaili Rusli; Harapan Tua Ricky Freddy; Abdul Sadad; Omar Farrakhan Tampubolon (Jurnal Ilmiah Global Education, 2026)
This qualitative study investigates the dynamics of collaborative waste management in Dumai City, Indonesia, utilizing the Triple Helix framework to analyze interactions between government, private sector, and community actors. Data collected through in-depth interviews with multiple stakeholders reveal significant challenges in waste governance, including irregular waste collection services, limited infrastructure, and inadequate public awareness of waste separation practices. Despite these obstacles, emerging initiatives demonstrate potential for improvement: community-led composting practices, private sector involvement through CSR programs and technology adoption (Masaro ITB system), and localized collaboration models. However, the study identifies critical barriers such as insufficient inter-agency coordination, cultural resistance to behavioral change, and underutilization of local knowledge. The research concludes that effective waste management in Dumai requires a more integrated approach that strengthens institutional frameworks, enhances community capacity building, and promotes technological innovation adapted to local contexts. These findings contribute to the broader discourse on sustainable waste governance in developing coastal cities and offer practical insights for policymakers seeking to implement collaborative environmental management strategies.